Hybrid tool with both fixed-abrasive and loose-abrasive phases. Issue 1 (2015) - Yamaguchi, Hitomi; Nteziyaremye, Valens; Stein, Max; Li, Weisi
Abstract The use of multiple pole tips in a Magnetic Abrasive Finishing (MAF) system allows for shorter processing times, but it can also exacerbate any difficulties encountered in abrasive insertion and distribution. This paper proposes a hybrid tool that initially works as fixed abrasive but works as loose abrasive once the abrasive binder dissolves into the lubricant. The fixed-abrasive configuration simplifies the abrasive insertion, and the loose-abrasive configuration ensures the abrasive uniform distribution along the workpiece surface. The internal finishing of needles demonstrated that the hybrid tool saves about 80% abrasive insertion time while achieving a smooth surface equivalent to the conventional MAF method.